2012
DOI: 10.1002/iub.598
|View full text |Cite
|
Sign up to set email alerts
|

ROCK1 induces ERK nuclear translocation in PDGF‐BB‐stimulated migration of rat vascular smooth muscle cells

Abstract: SummaryIt has been known that Rho-associated protein kinase (ROCK) signaling regulates the migration of vascular smooth muscle cells (VSMCs). However, the isoform-specific roles of ROCK and its underlying mechanism in VSMC migration are not well understood. The current study thus aimed to investigate the roles of ROCK1/2 and their relationship to the MAPK signaling pathway in platelet-derived growth factor (PDGF)-induced rat aorta VSMC migration by manipulating ROCK gene expression. The results revealed that R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…In ROCK1 knockout mice, an open eyelid at birth or omphalocele in neonates was observed (Shimizu et al, 2005), whereas in ROCK2 knockout mice, hemorrhage in embryos or hematoma in embryos and neonates was observed (Thumkeo et al, 2003). Moreover, in vitro studies using Rho-kinase isoform-specific knockdown suggest that ROCK1 and ROCK2 play distinct roles in fibroblasts (Yoneda et al, 2005(Yoneda et al, , 2007, keratinocytes (Lock and Hotchin, 2009;Lock et al, 2012), preadipocytes (Noguchi et al, 2007), adipocytes (Chun et al, 2012), endothelial cells (Mong and Wang, 2009;Bryan et al, 2010;Shimada and Rajagopalan, 2010), vascular smooth muscle cells (Zhao et al, 2012) and cancer cells Inaba et al, 2010;Vega et al, 2011). Other functional differences between ROCK1 and ROCK2 have been reviewed (Noma et al, 2006;Shi and Wei, 2007;Nunes et al, 2010;Satoh et al, 2011).…”
Section: Cytoplasmmentioning
confidence: 99%
“…In ROCK1 knockout mice, an open eyelid at birth or omphalocele in neonates was observed (Shimizu et al, 2005), whereas in ROCK2 knockout mice, hemorrhage in embryos or hematoma in embryos and neonates was observed (Thumkeo et al, 2003). Moreover, in vitro studies using Rho-kinase isoform-specific knockdown suggest that ROCK1 and ROCK2 play distinct roles in fibroblasts (Yoneda et al, 2005(Yoneda et al, , 2007, keratinocytes (Lock and Hotchin, 2009;Lock et al, 2012), preadipocytes (Noguchi et al, 2007), adipocytes (Chun et al, 2012), endothelial cells (Mong and Wang, 2009;Bryan et al, 2010;Shimada and Rajagopalan, 2010), vascular smooth muscle cells (Zhao et al, 2012) and cancer cells Inaba et al, 2010;Vega et al, 2011). Other functional differences between ROCK1 and ROCK2 have been reviewed (Noma et al, 2006;Shi and Wei, 2007;Nunes et al, 2010;Satoh et al, 2011).…”
Section: Cytoplasmmentioning
confidence: 99%
“…However, few studies have explored any potential cross talk between each of these signaling systems. A few studies have shown that ROCK 1 deficiency can impair MAPK signaling, however, little is known regarding the effects of ERK1/2-MAPK deficiency on the ROCK 1 signaling pathway1845. The current work indicates that upon exposure to TGF-β, ERK1/2 phosphorylation in cardiac fibroblasts increases within 30 mins, and that the application of the ERK1/2 phosphorylation inhibitor PD98059 inhibits ROCK 1 and MRTF-A nuclear translocation.…”
Section: Discussionmentioning
confidence: 65%
“…The MAPK pathway is activated by TGF-β in myofibroblasts and is a known downstream factor of TGF-β that mediates ROCK 1 expression in tissues1819.…”
mentioning
confidence: 99%
“…A signalling pathway between PKCs and mitogen-activated protein kinase (MAPK) seems crucial for the initiation and progression of VSMC proliferation. For example, mitogens can activate MAPK via inducing the kinase translocation from the cytosome to the nucleus where it promotes gene expression and cell growth in undifferentiated cultured VSMCs as well as in differentiated contractile VSM [4], and attenuation of the MAPK pathway by Labedipinedilol-A can inhibit cell proliferation, which is regulated by Ca 2+ and PKC [5]. The PKC family is generally divided into three groups, differing in the enzymes' cofactor requirements: conventional (c) PKCs (including α, β I, II and γ isoforms) require calcium and diacylglycerol (DAG) for activation; novel (n) PKCs (comprising δ, θ, ε and η isoforms) are activated by DAG; and atypical (a) PKCs include ζ and λ/ι isoforms and are dependent on phosphatidylserine but are not affected by DAG, phorbol ester, or Ca…”
Section: Introductionmentioning
confidence: 99%